New, cheap and efficient synthetic Zeolite-X decontaminant agent from fly ash for heavy metal toxicity - M. A., Tsabih; A. O., Mohamed; Ahmed, Omer Abdalla; Ali, Ayman A. A.; M., Ghada; Nour, A. H.; Ahmed, Aimun A. E. (JOCPR, 2018)
The study aimed to synthesize and characterize a zeolite type X from recycling fly ash by hydrothermal treatment in the presence of sodium hydroxide and used it as decontaminant agent to remove some heavy metals (Zn+2, Pb+2 and Cu+2) from standard aqueous solution by adsorption process. The prepared zeolite from fly ash by hydrothermal process was successively analyzed and characterized by X-ray Diffraction (XRD) and Fourier transfer infra-red (FTIRs) spectroscopy. Atomic absorption was used to determine the adsorption kinetic isotherm profile for the synthetic Zeolite-X, whilst the order of reaction was determined by application of Langmuir and Freundlich isotherm models. The results showed that, the produced yield of Zeolite-X (Potassium Sodium Aluminum Silicate, Chemical formula: (K57Na42(Al96 Si96 O38) was (74.8%). The kinetic isotherm studies showed time-dependent heterogenous adsorption profile following Freundlich isotherm model with first order kinetic reaction. Finally, we concluded that, the amount of Zeolite-X produced by hydrothermal process from Sudanese fly ash was found to be greater than others and was useful as a very sensitive and efficient synthetic decontaminant for elimination of heavy metals from aqueous solutions in very low concentrations. The preferable heterogeneous Freundlich isotherm model was more applicable for this synthetic Zeolite-X than the homogenous Langmuir model. It was strongly recommended to use Zeolite X in industrial areas as well as areas sufferings form water pollution by heavy metals.